54.6k views
0 votes
For the Transformation T write the T-1

T: (x, y) = (x + 4, y + 3)
Т-1 (x, y) -
(x+3, y + 2)
(x-4, y-3)
(x+, y + 3)

User Abraham P
by
4.4k points

1 Answer

2 votes

Answer:

(T - 1)(x, y) = (x - 4, y - 3)

Explanation:

For a given transformation:

T(x, y) = (x', y')

the inverse transformation is defined by:

(T - 1)(x', y') = (x, y)

So, if our transformation is:

T(x, y) = (x + 4, y + 3)

Then for the inverse transformation, we should have:

(T - 1)(x + 4, y + 3) = (x, y)

So the inverse transformation reduces the x-value by 4, and reduces the y-value by 3.

Writing the inverse transformation for a generic (x, y) point, we get:

(T - 1)(x, y) = (x - 4, y - 3)

User Flavio Caduff
by
4.4k points